Unburdening dementia – a basic social process grounded theory based on a primary care physician survey from 25 countries. (2nd July 2020) - Petrazzuoli, Ferdinando; Vinker, Shlomo; Palmqvist, Sebastian; Midlöv, Patrik; Lepeleire, Jan De; Pirani, Alessandro; Frese, Thomas; Buono, Nicola; Ahrensberg, Jette; Asenova, Radost; Boreu, Quintí Foguet; Peker, Gülsen Ceyhun; et al.
Abstract: Objective: To explore dementia management from a primary care physician perspective. Design: One-page seven-item multiple choice questionnaire; free text space for every item; final narrative question of a dementia case story. Inductive explorative grounded theory analysis. Derived results in cluster analyses. Appropriateness of dementia drugs assessed by tertiary care specialist. Setting: Twenty-five European General Practice Research Network member countries. Subjects: Four hundred and forty-five key informant primary care physician respondents of which 106 presented 155 case stories. Main outcome measures: Processes and typologies of dementia management. Proportion of case stories with drug treatment and treatment according to guidelines. Results: Unburdening dementia – a basic social process – explained physicians' dementia management according to a grounded theory analysis using both qualitative and quantitative data. Unburdening starts with Recognizing the dementia burden by Burden Identification and Burden Assessment followed by Burden Relief . Drugs to relieve the dementia burden were reported for 130 of 155 patients; acetylcholinesterase inhibitors or memantine treatment in 89 of 155 patients – 60% appropriate according to guidelines and 40% outside of guidelines. More Central and Northern primary care physicians were allowed to prescribe, and more were engaged in dementia management than Eastern and Mediterranean physicians according to cluster analyses. Physicians typically identified and assessed the dementia burden and then tried to relieve it, commonly by drug prescriptions, but also by community health and home help services, mentioned in more than half of the case stories. Conclusions: Primary care physician dementia management was explained by an Unburdening process with the goal to relieve the dementia burden, mainly by drugs often prescribed outside of guideline indications. Implications: Unique data about dementia management by European primary care physicians to inform appropriate stakeholders. Key points: Dementia as a syndrome of cognitive and functional decline and behavioural and psychological symptoms causes a tremendous burden on patients, their families, and society. We found that a basic social process of Unburdening dementia explained dementia management according to case stories and survey comments from primary care physicians in 25 countries. First, Burden Recognition by Identification and Assessment and then Burden Relief – often by drugs. Prescribing physicians repeatedly broadened guideline indications for dementia drugs. The more physicians were allowed to prescribe dementia drugs, the more they were responsible for the dementia work-up. Our study provides unique data about dementia management in European primary care for the benefit of national and international stakeholders.